Ecological Values in Poetry Worked by Students of Sabilillah Islamic Boarding School, Lamongan - Rosita, Devi Ayu; Nurhadi, Nurhadi; Roekhan , Roekhan (FKIP - Universitas Riau, 2026)
Ecological issues have gained increasing attention in educational contexts, particularly in Indonesian language learning, where literary activities can support environmental awareness and character education. This study examines the ecological values represented in poetry written by eighth-grade students of Sabilillah Islamic Boarding School (SIBS), Lamongan. Focusing on four ecological values human-environment relationships, environmental awareness, environmental responsibility, and environmentally caring actions this research employed a qualitative descriptive method using an ecocritical approach. The data consisted of 58 environmentally themed poems collected through intensive reading and note-taking techniques. The analysis was conducted by identifying ecological value indicators reflected in themes, diction, imagery, symbols, and moral messages. The findings reveal that students' poems portray nature as a vital life-support system and emphasize the interconnectedness between humans and the environment. Ecological values are expressed through respect for nature, moral appeals to protect the environment, and concrete actions such as conserving resources and maintaining environmental cleanliness. The study concludes that poetry is an effective medium for fostering ecological awareness and environmentally responsible character in Indonesian language learning, demonstrating students' capacity to articulate environmental concerns through literary expression.